PENDEKATAN WEBBED LEARNING PADA PEMBELAJARAN TEMATIK TERHADAP PESERTA DIDIK INKLUSIF DI MADRASAH - Hasan Baharun; Siska Ana Astriani (Al-Mudarris: Journal Of Education, 2019)
This paper presents the implementation of the webbed learning model on thematic learning on inclusive learners in Madrasah Ibtidaiyah Negeri 1 Probolinggo. Gathering normal students with inclusive students in the madrasah has many positive effects, such as arising from feeling nurturing, loving, and respecting between normal students and students with special needs. There is no treatment to choose a teacher's love for students' physical and mental differences, all must be equal and fair. Therefore, in order to streamline learning, a webbed learning approach is needed in the design of learning in heterogeneous classes. This research uses qualitative with case study. The results showed that the application of the webbed learning learning model on thematic learning of inclusive students at MIN 1 Probolinggo, used the scientific approach and active learning with the principle of joyful learning, which was carried out through; first, integration through student integration, second, integrated learning on the material, third, determining student activities, fourth, studying media and learning resources, fifth, culminating (sharing) in the form of learning evaluation.